Structure- and sequence-specificity of ozone degradation of supercoiled plasmid DNA. - Sawadaishi, K (Nucleic Acids Res, 1986)
Ozone-reactive sites on the nucleobase moieties in supercoiled pBR322 DNA were investigated by using sequencing procedures. Ozonolysis in the absence of salt resulted in degradation of thymine residues in the A + T rich region located at 3100-3400bp. In the presence of salt, such as NaCl or MgCl2, a conformational change of plasmid DNA was induced. Subsequently the thymine and guanine residues in the loop of the cruciform located at 3120bp and 3220bp were degraded. In addition, central thymine residues present in sequences GTA, GTT and ATA were also degraded. IMAGES: